KONSEP LIFELONG EDUCATION DALAM PANDANGAN ISLAM - Mujahidin, Mujahidin (State Institute of Islamic Studies (IAIN) Palu, 2009)
This research is library one. The approach used is theolo-normative analysis and socio-pedagogical one. The results indicate that the concept of Â lifelong education Â in Islam is a continual process beginning from womb to grave. The process covers the forms of formal, non formal and informal education, that take place at schools, family, and community. Islam even views that education to-be-born baby should be initiated prior to the marriage of parents. Therefore, Islam recommends that one marry a pious woman.Kata Kunci: lifelong education, pendidikan Islam, teologis-normatif, sosiologis-paedagogis